Comparison of Surface and Structural Properties of Carbonaceous Materials Prepared by Chemical Activation of Tomato Paste Waste: The Effects of Activator Type and Impregnation Ratio. (22nd November 2016) - Ozbay, Nurgul; Yargic, Adife Seyda
Abstract : Activated carbons were prepared by carbonization of tomato paste processing industry waste at 500°C followed by chemical activation with KOH, K2 CO3, and HCl in N2 atmosphere at low temperature (500°C). The effects of different activating agents and impregnation ratios (25, 50, and 100 wt.%) on the materials' characteristics were examined. Precursor, carbonized tomato waste (CTW), and activated carbons were characterized by using ultimate and proximate analysis, thermogravimetric analysis (TG/DTG), Fourier transform-infrared (FT-IR) spectroscopy, X-ray fluorescence (XRF) spectroscopy, point of zero charge measurements (p H P Z C ), particle size analyzer, scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, nitrogen adsorption/desorption isotherms, and X-ray diffraction (XRD) analysis. Activation process improved pore formation and changed activated carbons' surface characteristics. Activated carbon with the highest surface area (283 m 3 /g) was prepared by using 50 wt.% KOH as an activator. According to the experimental results, tomato paste waste could be used as an alternative precursor to produce low-cost activated carbon.